(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We have measured the \(1s2s2p ^4P^0_5/2\)-\(1s^22s ^2S_1/2\) magnetic quadrupole X-ray transition energy in Li-like Fe along with the \(1s2s ^3S_1\)-\(1s^2 ^1S_0\) transition energy in He-like Fe using multi channel doppler tuned spectrometer. These states have been produced through the interaction of 165 MeV Fe\(^12+\) ion beam with 100 \(μ\)g/cm\(^2\) thin carbon foil. Further we have measured the lifetime of \(1s2s2p ^4P^0_5/2\) level in Li-like Fe. The measured transition energy of \(1s2s ^3S_1\)-\(1s^2 ^1S_0\) is in good agreement with the available theoretical predictions and experimental measurements, whereas the measurement of \(1s2s2p ^4P^0_5/2\)-\(1s^22s ^2S_1/2\) energy is little lower than the theoretical estimations. However, the measured lifetime of \(1s2s2p ^4P^0_5/2\) level compares well with the theoretical predictions.